Taxonomic study of subfamily Nepetoideae (Lamiaceae) by polynomorphological approach. Issue 7 (12th March 2019) - Gul, Saba; Ahmad, Mushtaq; Zafar, Muhammad; Bahadur, Saraj; Sultana, Shazia; Begum, Najla; Shah, Syed Nasar; Zaman, Wajid; Ullah, Fazal; Ayaz, Asma; Hanif, Uzma
Abstract: The present study is insight into pollen morphology for characterizing species and their utility in the taxonomic separation of certain taxa of subfamily Nepetoideae (Lamiaceae) from Pakistan. The pollen micromorphology of 11 species of the Nepetoideae was analyzed and documented using light microscopy and scanning electron microscopy (SEM) for both qualitative and quantitative characteristics. Most species have hexazonocolpate pollen grains but trizonocolpate and tetrazonocolpate pollen with circular and oval amb were also rarely observed in Mentha spicata . The basic pollen shape in most of the studied species was subspheroidal but prolate grains were also observed in M. spicata, S. coccinea, and S. plebeia . The exine sculpturing of Nepetoideae pollen was taxonomically very informative particularly at subfamily level. Observations of exine sculpturing with SEM revealed various types of pollen grains: reticulate, bireticulate, microreticulate, perforate, aerolate, and gammate. The bireticulate type further subdivided into three subtypes based on the number of secondary lumina in each primary lumen and is characterized by varying characteristics of the secondary reticulum and primary muri. A significant variation was observed in colpus surface ornamentation. The maximum polar diameter was found in O. americanum (58 ± 5.8 μm) and the maximum equatorial diameter observed in O. basilicum (50.25 ± 1.37 μm). Pollen features of the studied species were discussed and compared based on the current taxonomical concepts. The results showed that pollen traits of the subfamily Nepetoideae was found significant to classify the taxa. Furthermore, pollen features provide additional evidence to distinguish macromorphologically similar taxa from each other. Abstract :